Climatic hazards in coastal Bangladesh non-structural and structural solutions - Paul, Bimal Kanti; Rashid, Harun 1943- (Butterworth-Heinemann, 2017)
Coastal Hazards in Bangladesh: Non-Structural and Structural Solutions provides a review of the study of Bangladesh’s coastal region, an area whose location and physical geography present the prefect microcosm for the study of coastal hazards and for the development of tactics that are applicable to regions around the world.